Analysis of the effect of organizational structure and culture on refugee problem and pandemic crisis management with artistic expression - Akkoyun, Bülent; Uyar, Saime (Technium Social Sciences Journal, 2020)
After the pandemic of COVID-19 and refugee problems that took hold of the world, the citizens and administrations of each country have been trying to survive by becoming nearly closed systems. This situation brought forward the societies that create the countries and their culture, which is the most important element of the societies, and deeply affected them. For this reason, it has been inevitable to examine the theoretical studies carried out so far. In this study, which has an interdisciplinary feature, it is aimed to reveal the effects of societies, which is the most extensive and widest one among organized structures and cultural differences, which constitute the basic building blocks of societies on the refugee and pandemic crisis management of countries. For this purpose, after making a theoretical evaluation of some societies in the light of studies conducted based on cultural differences, it has been revealed that these differences have strong effects on refugee and pandemic crisis management. On the other hand, communities and their cultures were also significantly affected by predicting that it would be permanent. To reach this result, a method with the lowest margin of error and art discipline was used as a methodology.